Cannabis use integrated with conventional cancer treatment (Research, Society and Development, 2022)
The present research aims at the use of cannabis integrated with conventional cancer treatment, considering that the increase in the number of people diagnosed with this pathology has led to the search for new alternatives to relieve symptoms caused by chemotherapy. Therefore, there was a need to demonstrate the efficacy and benefits, as well as the risks of the use of Cannabis sativa, based on scientific evidence, in order to safely promote the quality of health of individuals affected by this condition. Therefore, it was necessary to evaluate this new therapy, proving its activity for the relief of symptoms caused by chemotherapy in cancer patients, identifying the risks and benefits. A bibliographic research is then carried out using the integrative review method. Therefore, it is verified the relevance of this compound in the control of nausea and vomiting and analgesic activity, in addition to the anti-tumor action and decreased insomnia, anxiety and depression. This has imposed the finding that despite presenting therapeutic activities proven by research, there is a need for further studies to improve understanding of the drug, ensuring the efficacy and safety of cannabis use.